2020
DOI: 10.1088/1757-899x/742/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ferri-alginate (Fe-Alg) as Environmentally Friendly Catalyst on the Formation of Solketal from Glycerol and Acetone

Abstract: Alginate is a naturally occurring anionic carbohydrate polymer which could be coupled with metallic cationic molecules to form heterogeneous catalyst. However, the potency of the heterogeneous catalyst on the production of solketal was not explored. This research was proposed to investigate the potency of Ferri-Alginate (Fe-Alg) as a cheap and environmentally friendly catalyst in the solketal reaction. Fe-Alg was synthesized by reacting FeCl3 to sodium alginate with different concentrations (0.1 -0.5 M). Fe-Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…[26] The low price, good affordability and high Lewis acidity of Fe(III) salt make it a counter ion in heteropoly acid salt, which is widely used in this catalytic reaction. [27] Silva D. et al [28] also revealed the positive effect of homogeneous Fe(III) catalyst on the reaction. Overall, the unprecedented high activity, low load (up to 10 ppm), good ecotoxicological characteristics, and high activities of iron salt are expected to become convincing catalysts for the sustainable transformation of renewable byproducts in nontoxic solvents.…”
Section: Introductionmentioning
confidence: 93%
“…[26] The low price, good affordability and high Lewis acidity of Fe(III) salt make it a counter ion in heteropoly acid salt, which is widely used in this catalytic reaction. [27] Silva D. et al [28] also revealed the positive effect of homogeneous Fe(III) catalyst on the reaction. Overall, the unprecedented high activity, low load (up to 10 ppm), good ecotoxicological characteristics, and high activities of iron salt are expected to become convincing catalysts for the sustainable transformation of renewable byproducts in nontoxic solvents.…”
Section: Introductionmentioning
confidence: 93%
“…S. Zaher et al reported a new type of iron alginate as a cheap and environmentally friendly catalyst for the production of ketone from glycerol and acetone [33]. The low price, good affordability and high Lewis acidity of iron (III) salt make it a counter ion in heteropoly acid salt, which is widely used in this catalytic reaction [34][35][36]. Silva D. et al [37] also revealed the positive effect of homogeneous Fe(III) catalyst on the reaction.…”
Section: Introductionmentioning
confidence: 99%